2013
DOI: 10.1007/s12032-013-0732-3
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of Th17 cells in acute leukemia

Abstract: Th17 cells and their effector cytokines have emerged as important mediators in inflammatory and autoimmune diseases and serve as an ambitious field in current immunology research. Recent studies suggest a potential impact of Th17 cells on solid tumors but relatively little is known about their contribution in hematological malignancies. The current study was designed to investigate the possible involvement and clinical significance of circulating Th17 cells in acute leukemia. Flow cytometry was used to analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 29 publications
2
29
1
Order By: Relevance
“…15,16,[18][19][20][24][25][26][40][41][42][43][44][45][46] Leukemia on the other hand might provide an environment favorable for Th17 cells to suppress tumor growth. 32,38 Similarly, ovarian cancer might attract a tumor suppressing IL-17 response, as the majority of studies found a correlation with a favorable outcome. 28,69 A possible explanation might be that different microenvironments favor infiltration of or differentiation toward more or less tumor-promoting immune cell phenotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16,[18][19][20][24][25][26][40][41][42][43][44][45][46] Leukemia on the other hand might provide an environment favorable for Th17 cells to suppress tumor growth. 32,38 Similarly, ovarian cancer might attract a tumor suppressing IL-17 response, as the majority of studies found a correlation with a favorable outcome. 28,69 A possible explanation might be that different microenvironments favor infiltration of or differentiation toward more or less tumor-promoting immune cell phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…17,[24][25][26]31 One study showed a correlation between high IL-17 and improved survival in leukemia. 32 Four studies did not observe a significant correlation between high serum IL-17 levels and survival, [33][34][35][36] although one group did find a trend toward poor prognosis (p D 0.05). 36 Overall, a high amount of IL-17 protein in serum has predominantly been correlated with poor survival ( Table 2).…”
Section: Study Design and Selection Criteriamentioning
confidence: 92%
“…On the other hand our findings were more or less similar to that detected by T Miyagaki,et al 19 who reported that IL-17A not significantly elevated in lesional skin of cutaneous T-cell lymphoma. Also a recent study carried out in Oncology Center, Mansoura University reported that serum levels of IL-17 and IL-21 in untreated acute leukemia patients were significantly higher than in controls and correlated positively with levels of circulating Th17 cells 20 .…”
Section: Discussionmentioning
confidence: 91%
“…The level of Th17 cells in peripheral blood of cancer patients is frequently founded to be higher than that in normal control, which might suggest an underlying inflammatory status [35]. Interesting, the high Th17 cells sampled from peripheral blood of patients with leukemia was correlated with better survival [67,68], while high Th17 cells sampled from bone marrow of patients with leukemia was an indicator of worse survival [69].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we also investigated the impact of Th17 cells on OS in 10 studies with 727 patients (Fig 4.C) [18,19,56,[63][64][65][66][67][68][69]. The Th17 cells were identified by flow cytometery analysis in all included studies.…”
Section: Th17 Cells and Survivalmentioning
confidence: 99%